Detection Rate of Helicobacter Pylori Infection and Atrophic Gastritis Using Serological Markers “GastroPanel®” Among Employees of the National Medical Research Radiological Centre of the Ministry of Health of the Russian Federation - A. D. Kaprin; N. S. Sergeeva; S. S. Pirogov; I. I. Alentov; O. К. Yutsevich; V. I. Ryabtseva; G. F. Minibaeva; N. V. Marshutina; T. А. Karmakova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2024)
Aim: to evaluate, using the “GastroPanel®”, the frequency of detection of H. pylori infection and associated gastric diseases among doctors and medical staff of the National Medical Research Radiological Centre of the Ministry of Health of the Russian Federation, Moscow.Materials and methods. Employees of three branches of the National Medical Research Radiological Centre (n = 434, mean age — 48.5 ± 0.6 years) were examined using laboratory tests “GastroPanel®” (Biohit Oyj, Finland). The test results make it possible to identify infection of the stomach with H. pylori, hypo- and hyperacid conditions, as well as atrophic gastritis of the antrum and body of the stomach, as its precancerous conditions. Esophagogastroduodenoscopy (EGDS) for suspected atrophic gastritis was performed with an Olympus GIF-HQ190 video endoscope (Japan) in a narrow-spectrum mode with close focus (NBI Dual Focus).Results. The absence of pathological signs detected by “GastroPanel®” was established in 23.3 % of cases, hyperacid state — in 18.4 %, and hypoacid state — in 5.2 %. These disorders are classified as functional. Consequently, the conditional norm in total was identified in 46.9 % of observations. An increased level of antibodies to H. pylori was found in 43.3 % of those examined. Atrophic gastritis in the body of the stomach according to the results of the “GastroPanel®” was detected in 4.8 % of cases (median age — 59 years), in the antrum (or increased secretion of hydrochloric acid) — also in 4.8 % of cases (median age — 52 years). Within two months after laboratory diagnostics, EGDS was performed for 10 out of 15 patients examined at the P. Hertsen Moscow Oncology Research Institute in whom, based on the results of the “GastroPanel®”, the presence of atrophic gastritis in the antrum (or increased secretion of hydrochloric acid) was suspected. In 6 out of 10 cases, atrophic gastritis of the antrum was confirmed (in two of them, the atrophy extended to the body of the stomach and was assessed as severe). Of the 11 people with the “GastroPanel®” conclusion “Atrophic gastritis of the body of the stomach,” an endoscopic examination was carried out in 7 persons, and in all these cases the diagnosis was confirmed, and in two people the conclusion was made of severe atrophic pangastritis.Conclusion. “GastroPanel®” confirmed its high significance in identifying H. pylori infection and precancerous atrophic changes in the gastric mucosa. Regarding the occupational risks of infection among medical workers, we consider it advisable to conduct such screening without selecting an asymptomatic population.